2010
DOI: 10.2204/iodp.proc.322.101.2010
|View full text |Cite
|
Sign up to set email alerts
|

Expedition 322 summary

Abstract: Integrated Ocean Drilling Program (IODP) Expedition 322 is part of the Nankai Trough Seismogenic Zone Experiment (NanTro-SEIZE) and was designed to document characteristics of incoming sedimentary strata and upper igneous basement prior to their arrival at the subduction front. To accomplish these objectives, coring was conducted at two sites in the Shikoku Basin on the subducting Philippine Sea plate. Site C0011 is located on the northwest flank of a prominent bathymetric high (the Kashinosaki Knoll), whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 63 publications
4
112
0
Order By: Relevance
“…This is also true in the Nankai Trough subduction zone, as revealed by the recent Integrated Ocean Drilling Program (IODP) Expeditions 316, 322, and 333 Underwood et al 2010;Expedition 333 Scientists 2012), part of the Nankai Trough Seismogenic Zone Experiment (NanTroSEIZE). NanTroSEIZE IODP Expeditions 315, 316, 319, and 338 also revealed that the shallow (≤2,000 m below the seafloor) Nankai Trough accretionary prism is largely composed of claystone with subordinate siltstone, sandstone, and tuff Expedition 319 Scientists 2010;Strasser et al 2014).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…This is also true in the Nankai Trough subduction zone, as revealed by the recent Integrated Ocean Drilling Program (IODP) Expeditions 316, 322, and 333 Underwood et al 2010;Expedition 333 Scientists 2012), part of the Nankai Trough Seismogenic Zone Experiment (NanTroSEIZE). NanTroSEIZE IODP Expeditions 315, 316, 319, and 338 also revealed that the shallow (≤2,000 m below the seafloor) Nankai Trough accretionary prism is largely composed of claystone with subordinate siltstone, sandstone, and tuff Expedition 319 Scientists 2010;Strasser et al 2014).…”
Section: Introductionmentioning
confidence: 90%
“…Yellow arrows are convergence vectors between the Philippine Sea plate and Japan (Seno et al 1993;Heki 2007). The map in (a) is modified after Underwood et al (2010), while the seismic profile of (b) is provided by Y. Nakamura of the Japan Agency for Marine-Earth Science and Technology.…”
Section: C0009 C0009mentioning
confidence: 99%
See 1 more Smart Citation
“…We will use a combination of LWD at proposed Sites HSM-05 and HSM-18A, located in the Hikurangi Trough and frontal thrust, during Expedition 372 and coring during Expedition 375. These activities will be followed by a strategy of carefully coordinated sampling and postexpedition laboratory analyses (e.g., Screaton et al, 2009;Underwood et al, 2010). Proposed Site HSM-05A will target the entire sediment package on top of the Hikurangi Plateau.…”
Section: Hikurangi Subduction Margin: Hypotheses and Scientific Objecmentioning
confidence: 99%
“…This hole was suspended with a temporary observatory attached to a retrievable bridge plug (termed the "SmartPlug") to monitor temperature and pore pressure at the fault zone. Expedition 322 characterized the subduction inputs at Integrated Ocean Drilling Program Sites C0011 and C0012 (Underwood et al, 2010). Two more Stage 2 expeditions followed a year later.…”
Section: Nantroseize Drilling Projectmentioning
confidence: 99%